Description of Critical Thinking Ability at XI IPA 1 Grade of SMAN 7 Padang in Solving Chemistry Problems on Reaction Rate Material - Wella Aulia Putri; Latisma DJ (Entalpi Pendidikan Kimia, 2022)
During learning process students tend to be passive and memorize with teacher’s explanations. This causes students’ critical thinking skills in finding solutions problems that do not develop optimally. Qualitative descriptive research aims to describe students’ critical thinking at XI IPA 1 grade of SMAN 7 Padang skills in solving chemistry problems on reaction rate material. The research sampling technique used purposive sampling in the XI IPA 1 grade with 38 students. The research data will be analyzed using the qualitative analysis technique of the Miles and Huberman (1984) model consists of data reduction, data display and verification. The research instruments are problem test with 5 questions referring to critical thinking indicators by Ennis (1985) including elementary clarification, basic support, inference, advanced clarification, strategies tactics and interviewing selected students. The results showed that RF subjects of students with high critical thinking skills 4 critical thinking indicators, such as elementary clarification, inference, advanced clarification, strategy and tactics. AM subjects with medium critical thinking skills fulfill 3 critical thinking indicators, elementary clarification, basic support, and inference. While the subject of AZ students with low critical thinking skills only fulfills 2 critical thinking indicators, constist of advanced clarification ,strategy and tactics. Keywords: Critical Thinking Ability, Critical Thinking Problems, Reaction Rate